2007
DOI: 10.1074/jbc.m610461200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of Arg-Gly-Asp Helix Motifs in αvβ6 Integrin Ligands

Abstract: Data relating to the structural basis of ligand recognition by integrins are limited. Here we describe the physical requirements for high affinity binding of ligands to ␣v␤6. By combining a series of structural analyses with functional testing, we show that 20-mer peptide ligands, derived from high affinity ligands of ␣v␤6 (foot-and-mouth-disease virus, latency associated peptide), have a common structure comprising an Arg-Gly-Asp motif at the tip of a hairpin turn followed immediately by a C-terminal helix. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
169
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(178 citation statements)
references
References 38 publications
7
169
1
1
Order By: Relevance
“…Nephronectin also contains an auxiliary sequence LFEIFEIER required for the high affinity binding of nephronectin to the ␣8␤1 integrin, which functions in concert with an RGD motif (24). DiCara et al (25) reported that the interaction of latent TGF-␤1 with ␣v␤6 integrin is determined by an LXXI sequence immediately C-terminal to the RGD motif, in which two hydrophobic residues Leu-218 and Ile-221 are required for the high affinity binding of latent TGF-␤1 to the ␣v␤6 integrin. Our results show that Leu-218 is critically required for latent TGF-␤1 recognition by ␣v␤8 integrin, but Ile-221 is dispensable for recognition, because the substitution of Ile-221 with Ala did not affect the high affinity binding of latent TGF-␤1 to ␣v␤8 integrin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nephronectin also contains an auxiliary sequence LFEIFEIER required for the high affinity binding of nephronectin to the ␣8␤1 integrin, which functions in concert with an RGD motif (24). DiCara et al (25) reported that the interaction of latent TGF-␤1 with ␣v␤6 integrin is determined by an LXXI sequence immediately C-terminal to the RGD motif, in which two hydrophobic residues Leu-218 and Ile-221 are required for the high affinity binding of latent TGF-␤1 to the ␣v␤6 integrin. Our results show that Leu-218 is critically required for latent TGF-␤1 recognition by ␣v␤8 integrin, but Ile-221 is dispensable for recognition, because the substitution of Ile-221 with Ala did not affect the high affinity binding of latent TGF-␤1 to ␣v␤8 integrin.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin-To explore the molecular basis of the restricted ligand specificity of ␣v␤8 integrin, we focused on the LXXI sequence immediately following the RGD motif, because the LXXI sequence was required for the high affinity binding of latent TGF-␤1 to ␣v␤6 integrin in concert with the RGD motif (25,26). We constructed latent TGF-␤1 mutants, in which the Leu-218 and/or Ile-221 residues of the LXXI sequence were substituted with Ala, and we assessed their ability to bind to the ␣v␤8 integrin (Fig.…”
Section: Leu-218 Residue Immediately Following the Rgd Motif Is Requimentioning
confidence: 99%
See 1 more Smart Citation
“…Structural analysis of 20-mer peptides from the VP1 coat protein of FMDV and the latency associated peptide of TGFb1 revealed that secondary structure is also important for binding potency, in particular, an a-helix immediately proximal to the RGD hairpin that brings the two Leu residues in the consensus sequence together on the same face of the helix. 9 The potency of different peptides was also found to be related to the length and propensity of helix formation, and furthermore, NMR experiments revealed that the two Leu residues are in close contact with the integrin when the peptide is bound which suggests that the helix is present in the bound conformation of the peptide. 9 To enable further NMR-based studies into the structure, dynamics and binding interactions of peptide ligands for avb6, it was desirable to generate 15 N and 13 C isotopically labelled peptides.…”
Section: Introductionmentioning
confidence: 99%
“…9 The potency of different peptides was also found to be related to the length and propensity of helix formation, and furthermore, NMR experiments revealed that the two Leu residues are in close contact with the integrin when the peptide is bound which suggests that the helix is present in the bound conformation of the peptide. 9 To enable further NMR-based studies into the structure, dynamics and binding interactions of peptide ligands for avb6, it was desirable to generate 15 N and 13 C isotopically labelled peptides. Such an approach allows the use of more sophisticated multi-dimensional NMR and nucleus-selective editing techniques to provide more detailed information than possible with homonuclear 1 H NMR alone.…”
Section: Introductionmentioning
confidence: 99%